Acute whole apple consumption did not influence postprandial lipaemia: a randomised crossover trial. Issue 7 (14th April 2020) - Lin, Xinjie; Liddle, Danyelle M.; Neizer, Hannah R.; Robinson, Lindsay E.; Wright, Amanda J.
Abstract: Whole apples are a source of pectin and polyphenols, both of which show potential to modulate postprandial lipaemia (PPL). The present study aimed to explore the effects of whole apple consumption on PPL, as a risk factor for CVD, in generally healthy but overweight and obese adults. A randomised, crossover acute meal trial was conducted with seventeen women and nine men (mean BMI of 34·1 (sem 0·2) kg/m 2 ). Blood samples were collected for 6 h after participants consumed an oral fat tolerance test meal that provided 1 g fat/kg body weight and 1500 mg acetaminophen per meal for estimating gastric emptying, with and without three whole raw Gala apples (approximately 200 g). Plasma TAG (with peak postprandial concentration as the primary outcome), apoB48, chylomicron-rich fraction particle size and fatty acid composition, glucose, insulin and acetaminophen were analysed. Differences between with and without apples were identified by ANCOVA. Apple consumption did not alter postprandial TAG response, chylomicron properties, glucose or acetaminophen ( P > 0·05), but did lead to a higher apoB48 peak concentration and exaggerated insulin between 20 and 180 min ( P < 0·05). Overall, as a complex food matrix, apples did not modulate postprandial TAG when consumed with a high-fat meal in overweight and obese adults, but did stimulate insulin secretion, potentially contributing to an increased TAG-rich lipoprotein production.